Analysis of the Distribution of Potassium-stimulated Adenosine Triphosphatase Activity in Soybean Root - Travis, Robert L. (1979)
The distribution of activity of a potassium-stimulated ATPase associated with the plasma membrane was determined in 4-day-old soybean roots. Changes in protein-based specific activity of the enzyme coincided with developmental changes in the root. Activity was low in the region of the root cap, increased to a maximum in the meristematic region, decreased to a minimum as cell elongation proceeded, and then increased as lateral root development began. Analysis of the data indicated that fluctuations in enzyme activity can be described by a three-phase system which can be approximated by a linear-linear-linear piece-wise regression curve. The need for constructing a biological model to describe plasma membrane development is suggested.